DISRUPSI DIGITAL MARKETING SYARIAH: STUDI KASUS INOVATIF PROMOSI SKINCARE DI ERA DIGITAL - Anggryani, Lisa; Karmila Sari, Surya; Hasminiar; Amir, Muhammad Fakhri; Kamiruddin (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This research aims to explore the impact of digital marketing on consumer purchasing decisions in the skincare industry, especially in the context of marketing based on sharia principles. This study analyzes how digital promotional strategies, such as influencer marketing, electronic word of mouth (e-WOM), and the integration of Islamic values, influence consumer preferences and loyalty. The method used in this research is library research, with data collection through analysis of books, scientific articles and relevant digital sources, including industry reports and case studies of skincare companies. Data is analyzed descriptively to understand trends and changes in sharia digital marketing strategies. The research results show that digital marketing has changed marketing patterns from conventional systems to ones based on digital technology, which has an impact on increasing the affordability and effectiveness of promotions. In Indonesia, the use of social media as a means of marketing skincare products has increased significantly, with more than 70% of consumers influenced by influencer recommendations and e-WOM in their purchasing decisions. Apart from that, many skincare brands have adopted marketing strategies based on Islamic values, such as sincerity, honesty, meaningfulness and accountability. This strategy not only increases consumer trust, but also ensures that promotions are in line with Islamic ethical and moral principles. Thus, this research confirms that sharia digital marketing disruption not only creates efficiency in skincare marketing, but also builds emotional attachment with consumers through an approach that is in line with Islamic values